Computer Literacy in Early Childhood Education: Difficulties and Benefits in a 3-year-old Classroom - Berciano-Alcaraz, Ainhoa (2022)
Objective. In this work, we analyze the type of difficulties and arguments that three-year-old children show when they carry out tasks related to programming and educational robotics. Method. A theoretical design has been developed, and a sequence of activities has been implemented in a classroom of 3-year-old children. A case study was conducted with 8 children. Results. Among the results, we identified three types of difficulties, those derived from the characteristics of the robot, those associated with the action-instruction comprehension dimension of computational thinking, and those associated with the cognitive stage of the children. Conclusions. Based on the analysis of the arguments expressed in the development of the task, we conclude that the use of educational robots at early ages favors the development of computer literacy, and this makes its inclusion in classroom activities recommendable.